Ireland's future in the world demand on energy resources - Flood, Donal T. (Statistical and Social Inquiry Society of Ireland, 1954)
The experience of two world wars has led the more advanced nations to examine the growing demand on their energy resources. In the English speaking countries, with which the economy of this country is particularly involved, several studies have been published both on general and on specific aspects of the question, and the trend of much research and development work at present in progress indicates the importance that is attached to it at governmental level. The purpose of this paper is to examine some of this published material and to present in a non-technical way such data as may have a bearing on the future position of Ireland.
Read before the Society, 26 February 1954
Keywords: Energy resources; World energy demand; Ireland, Energy requirements; Energy, Ireland, Economic aspects; 314.15